CAUSES AND METHODS OF TREATMENT OF THE PHENOMENON OF VACUUM IN THE SPINE (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
: A diseased lumbar intervertebral vacuum disc void of any structurally intact tissue may be vertically unstable. A primary standalone endoscopic decompression and interbody fusion surgery in the treatment of vertical instability in patients with a vacuum disc may be a more reliable treatment than decompression alone.